2017
DOI: 10.1021/acsami.7b07611
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Wet Chemical Synthesis of Au NPs/TiH2/Nanocarved Ti Self-Supported Electrocatalysts for Highly Efficient H2 Generation

Abstract: Self-supported electrocatalysts are a new class of materials exhibiting high catalytic performance for various electrochemical processes and can be directly equipped in energy conversion devices. We present here, for the first time, sparse Au NPs self-supported on etched Ti (nanocarved Ti substrate self-supported with TiH) as promising catalysts for the electrochemical generation of hydrogen (H) in KOH solutions. Cleaned, as-polished Ti substrates were etched in highly concentrated sulfuric acid solutions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…These results reveal that the improved HER catalytic activity not only survives as long as the potential (current) is held constant at −0.7 V vs RHE, but also is ameliorated during the operation, a highly promising aspect for the catalyst's practical use over long term operation. Catalyst activation during long‐term cathodic processes was a reproducible phenomenon in this work, and formerly obtained in our laboratory 73‐77 …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…These results reveal that the improved HER catalytic activity not only survives as long as the potential (current) is held constant at −0.7 V vs RHE, but also is ameliorated during the operation, a highly promising aspect for the catalyst's practical use over long term operation. Catalyst activation during long‐term cathodic processes was a reproducible phenomenon in this work, and formerly obtained in our laboratory 73‐77 …”
Section: Resultssupporting
confidence: 67%
“…Catalyst activation during longterm cathodic processes was a reproducible phenomenon in this work, and formerly obtained in our laboratory. [73][74][75][76][77] The evolved hydrogen is expected to incorporate into the crystal structure of ZrO 2 NPs creating new defect (catalytically active) sites for the HER. 78 Hydrogen incorporation into the material structure may also break ZrO 2 NPs down due to the hydrogen insertion-induced stress/strain.…”
Section: Active Sites Density and Turnover Frequency Calculationsmentioning
confidence: 99%
“…Surface modifications of Ti species have been conducted to improve the catalytic performance. Amin et al prepared TiH 2 layers on a Ti substrate by cathodic polarization and H 2 SO 4 etching, for both methods markedly increase the HER performance. , Liu et al found the generation of titanium hydrides on a Ti-2 alloy during galvanostatic polarization in acidic solution, and electrochemical experiments indicated that the titanium hydrides can catalyze the HER …”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals and organic pollutants are often found in effluent; as a result, the removal of them is of great realistic significance with broad application prospects. Photocatalytic technology offers an opportunity to overcome the problem. − Titanium dioxide as a classical photocatalyst is widely used, but it has some shortcomings (low utilization of solar energy), which seriously limit its practical application. Therefore, designing a new and efficient photocatalyst to utilize visible light is the focus in the current study of photocatalysis. − Bismuth vanadate (BiVO 4 , n-type semiconductor) attracts increasingly bigger attention due to its excellent chemical stability, nontoxicity, and so on. , However, further improving photocatalytic performance is necessary due to its low ability to separate electron–hole pairs. − …”
Section: Introductionmentioning
confidence: 99%